Investigation of the multiple anchors approach in oligonucleotide microarray preparation using linear and stem–loop structured probes - Bordoni, Roberta (Oxford University Press, 2002)
Enzyme-mediated reactions are a useful tool in mutation detection when using a microarray format. Discriminating probes attached to the surface of a DNA chip have to be accessible to target DNA and to the enzyme (ligase or polymerase) that catalyses the formation of a new phosphodiester bond. This requires an appropriate chemical platform. Recently, an oligonucleotide hairpin architecture incorporating multiple phosphorothioate moieties along the loop has been proposed as an effective approach to solid-phase minisequencing. We have explored in depth several variables (stem length, number of phosphorothioates, stem–loop architecture versus linear structure) involved in this strategy by using a solid-phase ligation reaction. Microarrays were fabricated either from aminosilyl-modified glass or from aminated polymeric surfaces made of poly-lysine. Both platforms were bromoacetylated and reacted with thiophosphorylated oligonucleotides. The resulting microarrays were tested using either a synthetic template or a PCR-amplified 16S rRNA genomic region as the target sequence. Our results confirm the robustness of the proposed chemistry. We extend its range of application to solid-phase ligation, demonstrating the effectiveness of multiple anchors and suggest that linear oligonucleotides incorporating multiple phosphorothioates are equivalent to their hairpin-structured counterparts.